รูปแบบการสอนตามแนวคิดการเรียนรู้ฐานชุมชน ในรายวิชาออกแบบผลิตภัณฑ์พื้นถิ่น สำหรับนักศึกษาระดับปริญญาตรี - สุริยันต์ ปิยะทิพย์; พรมพันธุ์ อินทิรา (An Online Journal of Education, 2018)
The purposes of this research were to 1) study teaching model using community based learning in local product design course 2) develop the teaching model using community based learning in local product design course. Purposive sampling is applied with 4 groups of sample, including; 1) teaching specialists in Local product design 2) designer specialists in community product design 3) community leaders and 4) students in local product design course. This research uses questionnaire, observation form and field record as tool for data collecting. For the development of teaching model using community based learning, three experts in teaching of product design have commented and improved the teaching model using community based learning in local product design course. The results were 1) the studying teaching model from interviewing of teaching specialists, product designer specialists, community leaders and students who enroll in local product design course including the data from field observation shown that the purpose of the teaching model using community based learning should be clearly determined, select potential community and give appropriate period of time to learn with community; 2) the developing of the teaching model from comments of teaching experts shown that teaching model can encourage student’s skills in identity analysis, identity of community, understanding more about context of community and can further develop their own design.